First observation of methane photochemical generation from an N, N-dimethylamino-substituted arene: the case of 4-(N, N-dimethylamino)benzaldehyde (DMABA). Issue 39 (29th September 2016) - Kuş, Nihal; Sharma, Archna; Fausto, Rui
Abstract: The first observation of methane photochemical production from an N, N -dimethylamino-substituted arene (DMABA: 4-( N, N -dimethylamino)benzaldehyde) is described. UV irradiation ( λ >298 nm) of DMABA isolated in a solid low temperature (10 K) argon matrix was found to lead to major unimolecular fragmentation of the compound to methane and 4-(methylideneamino)benzaldehyde (4MAB). This reaction channel was found to be strongly preferred over the photochemical decarbonylation, which is usually found as the major photochemical transformation undergone by matrix-isolated benzaldehydes. New structural and spectroscopic data for both the reactant molecule (DMABA) and its major observed photoproduct (4MAB) are also presented. The experimentally obtained results are supported by an extensive set of quantum chemical calculations undertaken using both ab initio (MP2) and density functional theory (DFT) methods. Graphical abstract: